ChemInform Abstract: [3 + 2]‐Annulations of N‐Alkyl‐3‐Substituted Indoles with Quinone Monoketals Catalyzed by Broensted Acids. Issue 20 (April 2016) - Chai, Zhuo; Chen, Jia‐Nan; Liu, Zhen; Li, Xue‐Fei; Yang, Pei‐Jun; Hu, Ji‐Ping; Yang, Gaosheng
Abstract: A novel method is elaborated for the synthesis of benzofuro[2, 3‐b]indolines (III) and (V) by [3 + 2]‐annulation of N‐alkyl‐3‐substituted indoles with quinone monoketals (II) in the presence of (‐)‐CSA as catalyst.